Implementation of Law No. 20 of 2001 on Corruption of Kopo Village Funds - Indah Nova Komalasari; Siti Ulfa; Yuli Adha Hamzah (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze the forms of misuse of village funds and the application of law to corruption crimes through case studies of court decisions. The method used is descriptive analytical with a normative juridical approach. The novelty of this study lies in its focus on analyzing court decisions in village fund corruption cases, which have rarely been studied in depth. The results of the study indicate various modes of misuse of village funds, ranging from abuse of authority to manipulation of accountability reports, which have serious impacts on state finances and village governance. The study concludes that the application of law in court decisions can be an important instrument in strengthening efforts to eradicate corruption.